"IMPROVING STUDENTS' LISTENING COMPREHENSION THROUGH TEACHER'S STORYTELLING IN TEACHING NARRATIVE TEXT" (A Classroom Action Research at the Eleventh Grade Of SMA 3 Boyolali in Second Semester 2009/2010 Academic Year) - MUSLIKATI, ASRINI (2011)
The students' problem was that most of them have low capability in listening competence, especially in comprehend narrative text. They are easy to be panic when they do not understand the meaning of the word they heard and the result is they are not motivated in joining the listening class so their score in listening is low. The objectives of the study are: (1) to find out whether teacher's storytelling technique can improve students' listening competence, (2) to find out the effectiveness of teacher's storytelling in teaching listening. Storytelling technique is a technique which was used by our ancestor to deliver the massage and gave moral value. By using teacher's storytelling technique, the writer wanted to solve the problems of students in listening class. Firstly, by using teacher's storytelling, students are more interested in listening class. After the students are interested in listening class, it is hopefully increase their motivation in following the listening class and in understanding the oral text. Secondly, Teacher's storytelling can increase the active participation of students in listening so that it can promote their listening skill. The study shows that teacher's storytelling gives some positive effects: (1) From the result of the test, in the first cycle, second cycle, and third cycle, students made a positive improvement. The average score of pre-test is 59, cycle 1 is 65.91, cycle 2 is 72.05, and cycle 3 75.45. The total students who gained passing grade improved significantly, from 28.21% in pre-test to 85.71 to post-test cycle 3. (2) Teacher's storytelling is effective in teaching listening. Most students participate well during the process of teaching and learning. They were motivated to follow the lesson, more focus on lesson, participate actively, eager to express their opinion, and cooperate in group. Therefore, it is suggested that English teachers apply this technique as one of the alternatives that can be used in teaching listening skill. Besides, it is also suggested to future researchers conduct similar study by using Teacher's storytelling on different setting and subjects to see whether the technique is also effective and applicable to be implemented in improving students' listening skill. For other researchers, it is recommended to do further research about the use of teacher's storytelling technique in the teaching of English.